Acceptability of patient education for hypertension self-management among healthcare providers and beneficiaries in South Africa, 2024: A qualitative study - Xoliswa Simelane; Juliana Kagura; Athini Nyatela; Samanta T. Lalla-Edward (African Journal of Primary Health Care & Family Medicine, 2025)
Background: The prevalence of hypertension (HTN) is increasing among people living with human immunodeficiency virus (HIV). Self-management is vital for improving health outcomes and preventing disease progression. While education for HTN self-management has been implemented in South Africa, little is known about its acceptability.